2019
DOI: 10.1371/journal.pone.0227153
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of Aloe Vera-derived plant-based cell in powering wireless device for remote sensor activation

Abstract: It is well proven that electrical energy can be harvested from the living plants which can be used as a potential renewable energy source for powering wireless devices in remote areas where replacing or recharging the battery is a difficult task. Therefore, harvesting electrical energy from living plants in remote areas such as in farms or forest areas can be an ideal source of energy as these areas are rich with living plants. The present paper proposes a design of a power management circuit that can harness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The CAM process allows them to withstand drought because their stomata open only at night to prevent the water from escaping via evaporation in the hot sun [41]. Researchers have paid attention to harvesting electrical energy from Aloe vera plants [42][43][44]. The major disadvantages of Aloe vera plants are that once the electrodes are inserted in leaf, leaf dyes faster and its survival rate is very short due to chemical reaction between electrode and the gel of Aloe vera despite its hardness and unique self-repairing ability.…”
Section: Introductionmentioning
confidence: 99%
“…The CAM process allows them to withstand drought because their stomata open only at night to prevent the water from escaping via evaporation in the hot sun [41]. Researchers have paid attention to harvesting electrical energy from Aloe vera plants [42][43][44]. The major disadvantages of Aloe vera plants are that once the electrodes are inserted in leaf, leaf dyes faster and its survival rate is very short due to chemical reaction between electrode and the gel of Aloe vera despite its hardness and unique self-repairing ability.…”
Section: Introductionmentioning
confidence: 99%
“…33 Studies of different metal electrodes embedded into cacti species reported that the highest electrochemical performance can be achieved by using copper and zinc electrodes in Aloe vera, 34 with the voltage enhanced by connecting multiple leaves. 31,34 Rather than exploiting the internal electrolytes of Cacti species to fabricate galvanic cells, other studies have shown the potential of such plants to provide the nutrients for soil bacteria for plant-MFC type energy production. 35,36 In such systems, organic molecules produced by photosynthesis are released via degraded roots enabling the survival of bacteria, which can be utilized to produce electricity by performing EET to donate electrons to an anode that is embedded in the soil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The thick cuticle protects the leaf from severe water loss limiting the release of water and biological metabolites that exist inside the inner aqueous environment of the leaf. The internal solution is quite complex and dynamic, containing polysaccharides, lipids, amino acids, metabolites, minerals, and proteins . Previous studies have indicated that the complex internal water-based solution could serve as an electrolyte and even provide a source of current.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations